Influencia de la capacitación del talento humano en el mejoramiento del servicio al cliente de las pymes del cantón Quevedo, año 2023 - Mena Subiaga, Gabriela Rocio (2024)
Customer service has become a determining factor for the success of small and medium-sized enterprises (SMEs), for this reason, understanding and improving the training of human talent in customer service becomes of vital importance for the sustainable development of these organizations. The objective of this research is to determine the influence of human talent training on the improvement of customer service in SMEs in the Quevedo canton, year 2023. The research techniques implemented were the survey of a finite sample of 234 owners and employees and the same number of clients of SMEs in the Quevedo canton, to whom a questionnaire was applied under the SERVPERF model. And an interview with the president of the Chamber of Commerce of the Quevedo canton. SMEs in Quevedo face challenges in staff training, with a need for greater regularity and updating in internal programs and inconsistent implementation of personalized programs. There are barriers in feedback and the use of technology, and resistance to training must be overcome with better communication and planning. Although evaluation models such as SERVPERF are key to identifying deficiencies, the results show dissatisfaction with service reliability, staff responsiveness, security and empathy, indicating an urgent need for improvements in the quality of customer service. Therefore, it is recommended to implement a comprehensive plan to improve the quality of customer service in SMEs in the Quevedo canton that addresses the deficiencies identified in each dimension evaluated by the SERVPERF model